On the algebra of derivations of some nilpotent Leibniz algebras - L.A. Kurdachenko; M.M. Semko; V.S. Yashchuk (Researches in Mathematics, 2023)
We describe the algebra of derivations of some nilpotent Leibniz algebra, having dimensionality 3.